Attentional Profiles and White Matter Correlates in Attention-Deficit/Hyperactivity Disorder Predominantly Inattentive Type - Rossi, Adriana Suzart Ungaretti; Moura, Luciana Monteiro de; Mello, Claudia Berlim de; Souza, Altay Alves Lino de; Muszkat, Mauro; Bueno, Orlando Francisco Amodeo (Frontiers in Psychiatry, 2015)
Attention-deficit/hyperactivity disorder (ADHD) is a widely studied neurodevelopmental disorder. It is a highly heterogeneous condition, encompassing different types of expression. The predominantly inattentive type is the most prevalent and the most stable over the lifetime, yet it is the least-studied presentation. To increase understanding of its cognitive profile, 29 children with Attention-deficit/hyperactivity disorder of predominantly inattentive type (ADHD-I) and 29 matched controls, aged 7 to 15 years, had their attentional abilities assessed through the Conners’ Continuous Performance Test. Diffusion tensor imaging data were collected for all of the participants using a 3.0 Tesla MRI system. Fractional anisotropy values were obtained for 20 fibre tracts, and brain-behaviour correlations were calculated for 42 of the children. The ADHD-I children differed significantly from the typically developing children with respect to attentional measures, such as the ability to maintain response-time consistency throughout the task (Hit RT SE and Variability), vigilance (Hit RT ISI and Hit RT ISI SE), processing speed (Hit RT), selective attention (Omissions), sustained attention (Hit RT Block Change), error profile (Response Style) and inhibitory control (Perseverations). Evidence of significant differences between the ADHD-I and the typically developing participants was not found with respect to the mean FA values in the fibre tracts analysed. Moderate and strong correlations between performance on the attention indicators and the tract-average fractional anisotropy values were found for the ADHD-I group. Our results contribute to a better characterization of the attentional profile of ADHD-I individuals and suggest that in children and adolescents with ADHD-I, attentional performance is mainly associated with the white-matter structure of the long associative fibres that connect anterior-posterior brain areas.